Comparative analysis of deforestation between the years 2019 to 2023, in the mucipality of Altamira (Research, Society and Development, 2024)
With the population increase, several demands for natural resources are generated, causing environmental changes that affect the landscape Altamira suffered a high population and migratory impulse with the construction of the Transamazônica highway (BR 230). Given the above, the present study aimed to carry out a comparative analysis of deforestation in the municipality of Altamira-PA through MapBiomas alert. The municipality of Altamira is located in the west of the state of Pará. From the MapBiomas Alert project, it is possible to export data on deforested areas, making it possible to analyze the evolution of these areas per year, which helps to compare the years with the highest and lowest rates of deforestation. Analyzes carried out show an increase in deforested areas in the municipality of Altamira. In the year 2021 there was the highest number of deforested areas corresponding to 74,612.0 per area. However, in 2022 there was a reduction in deforested areas, which shows the importance of generating these alerts. In 2019, the deforested area was 56,484.1. In 2020 the number rose to 62,221.1. Which made the municipality rank first among the 10 municipalities in Brazil with the largest deforested areas. This study reveals the considerable increase in recent years of deforested areas in the municipality of Altamira, which shows that measures must be taken to minimize these damages, since this affects biodiversity, since, with the removal of vegetation cover, there is an imbalance in the fauna and flora. compromising the disappearance of species.